2014
DOI: 10.5435/00124635-201402000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Composite Bone Models in Orthopaedic Surgery Research and Education

Abstract: Composite bone models are increasingly used in orthopaedic biomechanics research and surgical education-applications that traditionally relied on cadavers. Cadaver bones are suboptimal for myriad reasons, including issues of cost, availability, preservation, and inconsistency between specimens. Further, cadaver samples disproportionately represent the elderly, whose bone quality may not be representative of the greater orthopaedic population. The current fourth-generation composite bone models provide an accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…To model osteoporosis, demineralization can be performed using reagents such as hydrochloric acid and hydrogen peroxide, but the models prepared using these methods differ from the pathological process of human osteoporosis, which is more like osteomalacia ( Elfar et al, 2014 ; Stewart et al, 2020 ). EDTA is a chelating agent that binds to the metal ion Ca 2+ and acts more slowly, preserving the natural biological structure of collagen better than the stronger and faster acting hydrochloric or nitric acids ( Lee et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…To model osteoporosis, demineralization can be performed using reagents such as hydrochloric acid and hydrogen peroxide, but the models prepared using these methods differ from the pathological process of human osteoporosis, which is more like osteomalacia ( Elfar et al, 2014 ; Stewart et al, 2020 ). EDTA is a chelating agent that binds to the metal ion Ca 2+ and acts more slowly, preserving the natural biological structure of collagen better than the stronger and faster acting hydrochloric or nitric acids ( Lee et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because fresh cadaver metacarpal bones with similar bone strength are difficult to obtain, this study adopted artificial metacarpal bones for experiments by referring to a previous study [30] and a report published by the American Society for Testing and Materials. On the basis of previous experimental procedures, [31][32][33] we conducted cantilever bending tests to verify fixation effectiveness in which maximum fracture force and stiffness, 2 common indicators of fixation ability, [14,[33][34][35] were measured.…”
Section: Discussionmentioning
confidence: 99%
“…This study has several limitations. First, like most related studies, [30,31,33] we did not use fresh cadaver metacarpal bones but instead used artificial ones. Additionally, cantilever bending tests were conducted by referring to several studies.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the biomechanical properties of fourth-generation composite femurs under bending, axial and torsional loading were similar to those of cadaveric specimens, with less variability than that in cadaveric specimens ( Elfar et al, 2014 ). Referring to the efficacy analysis of Stoffel et al, 2017 ( Stoffel et al, 2017 ), we selected 10 Sawbone femurs (left, fourth generation, Pacific Research Laboratories, Washington, United States of America) to mimic a Pauwels type III femoral neck fracture.…”
Section: Methodsmentioning
confidence: 99%
“…A study showed that the biomechanical properties of fourthgeneration composite femurs under bending, axial and torsional loading were similar to those of cadaveric specimens, with less Frontiers in Bioengineering and Biotechnology frontiersin.org variability than that in cadaveric specimens (Elfar et al, 2014).…”
Section: Biomechanical Testingmentioning
confidence: 99%